EVALUATION OF BENZYLIDENE-ACETONE ANALOGUES OF CURCUMIN AS ANTITUBERCULOSIS - Safitri, Cikra Ikhda Nur Hamidah; Ritmaleni, Ritmaleni; Rintiswati, Ning; Sardjiman, Sardjiman; Kaneko, Takushi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this research is to evaluate the effect of benzylideneacetone analog of curcumin against Mycobacterium tuberculosis (MTB) H37Rv. Method: The activity of benzylideneacetone analog of curcumin is evaluated using mycobacteria growth indicator tube (MGIT) method and microplate alamar blue assay (MABA) method. The compound of minimum inhibitory concentration (MIC) is defined as the minimum concentration of drugs which really inhibit the growth of MTB. Result: The MIC compound of 1,5-bis(3,4-dichlorophenyl)-1,4-pentadiene-3-one (C9) and 1,5-bis(3-chlorophenyl)-1,4-pentadiene-3-one (C10) can inhibit the bacteria of MTB at the concentration of 500 Î¼g/ml using MGIT method. Based on MABA method, it can be obtained similar MIC value of C9 compound and C10 compound that are 187.5 Î¼g/ml. Conclusion: C9 and C10 have antituberculosis activity. Benzylideneacetone analog of curcumin which has chlor moiety has a better activity in inhibiting MTB, but it still needs further research to make it become a potent antituberculosis drug.